131I Intake and Regulatory Compliance Following Administration of Capsular 131I Sodium Iodide for Treatment of Thyroid Disorders. Issue 2 (February 2022) - Jafari, Mary Ellen; Paik, David S.
Abstract : Abstract: Intake of 131 I by nuclear medicine technologists and physician Authorized Users was evaluated using bioassay data from administration of 131 I sodium iodide in capsular form during a 5-year period. Maximum estimated annual intake of 131 I sodium iodide, based on bioassay measurements performed at 24 hours post administration, ranged from 10.9 to 35.6 kBq for all staff. Intake by Authorized Users was higher than that by nuclear medicine technologists due to state requirement for Authorized Users to physically administer therapeutic dosages of radiopharmaceuticals. All intake values were less than 10% of the 131 I thyroid ALI of 50 microcurie 3 (1, 850 kBq), indicating that monitoring may be discontinued for staff participating in routine administration of 131 I capsules in which volatilization is not suspected. Elimination of bioassay performance has permitted more flexibility in patient scheduling and improved workflow and efficiency.